Effects of earthquakes in Postojna cave system - Šebela, Stanka (Acta Carsologica, 2010)
Regarding the studied historic references there are sufficient proofs that during the 1st January 1926 earthquake (M=5.6) in Postojna cave system (Sala del Candore or Pralnica) a stalagmite column of 1 meter in diameter collapsed. This is a not so common event in karst caves and took place due to the close vicinity of the epicentre located at the SE end of Idrija Fault or at the Javorniki Mountain. During earthquakes in karst caves brontides are generally heard, but ground movement is rarely felt. Only strong and close earthquakes can be felt as ground shaking or waving inside the caves also, withsome possible collapses as well.